The Persistent Transboundary Problem in Marine Natural Resource Management - Liu, Owen R.; Molina, Renato (Frontiers in Marine Science, 2021)
Shared natural resources are vulnerable to overexploitation. Countries have established national borders on land and exclusive economic zones (EEZs) in the world's oceans in part to better control exploitation of local resources, but transboundary resources—those that span multiple national jurisdictions—are still subject to incentives for overextraction. We investigate the magnitude and distribution of this “transboundary problem” as it manifests in global fisheries. We show that internationally-shared fisheries exhibit lower relative abundance, on average, than those contained in single EEZs, even in the presence of extraction agreements and modern management practices. Additionally, for the first time we show that the degree of sharing—the number of countries sharing a resource and the spatial balance of each country's share—matters in driving the severity of the transboundary problem. Alleviating the transboundary problem for the fisheries we investigate would result in an estimated 4 to 17 million metric tons more fish in the ocean. In the future, growing human demand and climate change will likely exacerbate pressures on transboundary resources, requiring coordinated international governance solutions.